لترقية الطالبات على فهم كتاب القراءة الرشيدة بمعهد الزهرة العصري بيرون- آتشيه STUDY استخدام الأسلوب - Phonna, Raihanil; Suhaimi, Suhaimi; Yulistri, Yulistri (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2022)
Learning at Modern Pesantren Al-Zahrah with theory of branches and among the subjects taught is Muthalaah with the Book al-Qiraatu ar-raasyiidah. The Purpose of Muthalaah's Learning in Modern Pesantren Al-Zahrah is a form of reading practice, justifying and enriching the language and deepening Qawaid Nahwu-Sharf. Muthalaah's learning process usually takes place with lecture methods and sometimes some teachers use the Jigsaw method in the learning process. The percentage of outcomes of the learning is 40% of students complete and the remaining 60% unfinished. This is evidenced by the acquisition of their test scores under the category below average. They are not able to answer questions about text content and do not understand certain words. Based on this problem Researchers want to conduct research with the title